Isotretinoin induced dysuria: A case report and review of literature about urological effects of isotretinoin - Müge Göre Karaali (Galenos Publishing House, 2021)
Isotretinoin is often used in the treatment of severe acne. However, many adverse reactions were reported, including mucocutaneous, metabolic, neurological and psychiatric, ophthalmologic, hematologic side effects and teratogenicity. The mucocutaneous are the most common side effects and often develop in a dose-dependent manner. I present a case of a 20-year-old male with the unusual non-specific dysuria only and review the literature on the urological effects of isotretinoin.